The Flightless Man: Self-Awareness in Fakhr al-Din al-Razi - M. Zahit Tiryaki (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2020)
The flying man thought experiment upon which Avicenna grounds his theory of self-awareness (al-shu‘ūr al-dhātī) and justifies the argument that the soul is an immaterial, incorporeal and independent substance, has drawn as much interest in the modern era as it has in the classical Islamic and Latin worlds, spawning various interpretations on what to make of the experiment’s basic claim and purpose. Commentators of both traditions differ on the basic claim and purpose of the flying man experiment, depending the ontological and epistemological attitudes they emphasize. This study firstly tries to clarify the claim and purpose of the experiment, inasmuch as it forms the basis of Fakhr al-Dīn al-Rāzī’s criticisms. It proceeds to briefly point out the context of the experiment from Avicenna to al-Rāzī, and examine al-Rāzī’s comments and criticisms thereof. Since he rejects the claim that the soul is an immaterial, incorporeal and independent substance, it follows that al-Rāzī does not understand the term essence (dhāt) in self-awareness (al-shu‘ūr al-dhātī) in the same way as Avicenna, who through the experiment, argues the exact opposite. Al-Rāzī rather interprets essence directly as the self, from which he proceeds to develop a distinct understanding of self-awareness.